ORP3 phosphorylation regulates phosphatidylinositol 4-phosphate and Ca(2+) dynamics at plasma membrane–ER contact sites - Gulyás, Gergő (J Cell Sci, 2020)
Oxysterol-binding protein (OSBP)-related proteins (ORPs) mediate non-vesicular lipid transfer between intracellular membranes. Phosphoinositide (PI) gradients play important roles in the ability of OSBP and some ORPs to transfer cholesterol and phosphatidylserine between the endoplasmic reticulum (ER) and other organelle membranes. Here, we show that plasma membrane (PM) association of ORP3 (also known as OSBPL3), a poorly characterized ORP family member, is triggered by protein kinase C (PKC) activation, especially when combined with Ca(2+) increases, and is determined by both PI(4,5)P(2) and PI4P. After activation, ORP3 efficiently extracts PI4P and to a lesser extent phosphatidic acid from the PM, and slightly increases PM cholesterol levels. Full activation of ORP3 resulted in decreased PM PI4P levels and inhibited Ca(2+) entry via the store-operated Ca(2+) entry pathway. The C-terminal region of ORP3 that follows the strictly defined lipid transfer domain was found to be critical for the proper localization and function of the protein.